2009
DOI: 10.1080/15470140903178567
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study Examining the Influence of Conference Food Function on Attendee Satisfaction and Return Intention at a Corporate Conference

Abstract: For many conferences and events, increased attendee registration leads to increased profits for the hosting organization. Food functions, in particular, can be an effective tool to satisfy attendees and build attendance, as it empowers an attendee's sensory memory of an event. Nutritiously balanced food can enhance an attendee's learning ability. The purpose of this research was to identify factors that impact the attendee's satisfaction with conference food functions, and further, to understand an attendee's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 17 publications
0
20
1
1
Order By: Relevance
“…For example, food quality consistency was added in a study of theme restaurants in Singapore (MacLaurin & MacLaurin, 2000). Others items included: innovative food, for upscale restaurants in Spain (Soriano, 2002); accurate order, for chain restaurants (Gupta, McLaughlin & Gomez, 2007); correct menu and available utensils, for corporate internal training program meetings (Kim et al, 2009); and food security, for Chinese restaurants (Liu & Jang, 2009).…”
Section: Food Quality and Attributesmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, food quality consistency was added in a study of theme restaurants in Singapore (MacLaurin & MacLaurin, 2000). Others items included: innovative food, for upscale restaurants in Spain (Soriano, 2002); accurate order, for chain restaurants (Gupta, McLaughlin & Gomez, 2007); correct menu and available utensils, for corporate internal training program meetings (Kim et al, 2009); and food security, for Chinese restaurants (Liu & Jang, 2009).…”
Section: Food Quality and Attributesmentioning
confidence: 99%
“…Organizers of international conferences must understand the structure of its participant base, embrace the diverse backgrounds, needs, and incentives of its attendees, and strive to tailor conference activities and food functions to these distinct preferences and demands. In formulating corporate meeting food attributes, Kim et al (2009) considered the following three constructs: food content quality, menu selection, and recognition of personal preference. As shown in Table 1, food content quality and menu selection coincide with and sufficiently summarize food quality attribute items used in previous restaurant studies.…”
Section: Food Quality and Attributesmentioning
confidence: 99%
See 2 more Smart Citations
“…Chris Pentz, president of a group communications firm, concluded that after an event, the food is what will stay in the guests' minds, particularly factors such as variety, presentation, taste and timing (Kim et al, 2009;Namkung & Jang, 2007), and flexible planning of menus (Amer, 2004). Prior to an event, site selection criteria like local support and information is important (Fawzy & Samra, 2008).…”
Section: Service For Mice Guestsmentioning
confidence: 99%